Determinants of Informal Land Renting Decisions by A1 and A2 Farmers in Mashonaland East Province of Zimbabwe - Tatsvarei, Simbarashe; Mushunje, Abbyssinia; Ngarava, Saul; Makate, Clifton (Journal of Economics and Behavioral Studies, 2018)
Land rental markets are critical in developing economies as they contribute to efficiency, equity and welfare gains to farmers involved under conditions of low transaction costs. Despite lack of policy consistency in Zimbabwe, A1 and A2 farmers have been involved in these land rental markets, albeit in an informal manner. This study sought to establish the determinants of farmers’ decision to take part in these informal markets. A survey was carried out in Mashonaland East province with a sample of 339 households selected through multi-stage sampling methods and data analysed using a bi-variate Tobit model. Results showed that combined together, the proportion of farmers involved in informal land rental markets are as much as those not participating. Determinants of renting-in were identified as gender, household income, permanent labour, cultivated area, tenure certainty, irrigable land size and crop diversification. Factors affecting renting-out decisions were age, permanent labour, irrigable land size and crop diversification and these results are not in any way different from findings from previous studies. The conclusion was that household characteristics and land endowments factors were strong in decisions to rent-in land while land endowments factors were dominant in decisions to rent-out land. Any future considerations for formalising land rental markets should consider these important factors having a bearing on land rental decisions.